Luminescence spectroscopy and electronic structure of Eu³⁺-doped Bi-containing oxide compounds - Nedilko, S.; Chornii, V.; Hizhnyi, Yu.; Scherbatskyi, V.; Slobodyanik, M.; Terebilenko, K.; Boyko, V.; Sheludko, V. (Functional Materials, 2013)
The photoluminescence (PL) studies of the set of undoped and doped with Eu³⁺ ions Bi-containing oxide compounds BiPO₄, K₃Bi₅(PO₄)₆, K₂Bi(PO₄)(MoO₄) and K₅Bi(MoO₄)₄ as well as calculations of their electronic structures were performed. The intrinsic PL of undoped crystals was found under excitation in VUV and UV diapason of light (100–400 nm). The PL spectra possess several main components lying in the blue-green, green-orange and orange-red light diapasons (from 400 up to 850 nm). When Eu ions are incorporated into the crystals, the intrinsic PL diminishes and inner f–f PL of Eu³⁺ ions becomes dominant. Comparison of the PL excitation spectra with the data of calculated partial density of electronic states allowed distinguishing the role of excitation transitions in bismuth-oxygen polyhedrons (BiO₈ or BiO₆), phosphate (PO₄³⁻) and molybdate (MoO₄²⁻) groups. Observed intrinsic PL mainly originates from the excitation transitions in Bi – oxygen polyhedrons followed by the related backward radiation transitions. Very strong excitation energy transfer from bismuth-oxygen polyhedrons to Eu³⁺ ions was observed for all investigated Eu-doped compounds.